Analisis Faktor-Faktor Yang Mempengaruhi Harga Ikan Asin Di Pulau Baai Kota Bengkulu - Yulista Yulista; Herri Fariadi; Ana Nurmalia (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Salted fish commodities play a strategic role in increasing the added value of the surplus of fresh fish production in Bengkulu City. However, supply dynamics influenced by seasons, weather, production costs, and distribution chains, amidst high market demand, cause price fluctuations, so a comprehensive analysis of price determinants is important to maintain market stability and encourage increased welfare of coastal communities. This study aims to analyze the price level of salted fish and the factors that influence the price of salted fish on Baai Island, Bengkulu City. This study uses a quantitative method with a descriptive approach and multiple linear regression analysis. Data are obtained from 49 respondents consisting of consumers, traders, salted fish processors, and fishermen. The independent variables include product quality, consumer demand, production costs, and raw material availability, while the dependent variable is the price of salted fish. The results show that the price level of salted fish on Baai Island, Bengkulu City is Rp 23,503, which is included in the moderate category. The results of multiple linear regression analysis show that all variables influence the price of salted fish on Baai Island, Bengkulu City, they are product quality factors (XI), consumer demand (X2), production costs (X3), and availability of raw materials (X4).